The Effect Of Application Of Problem Based Learning Model On Critical Thinking Ability Students In Learning Ips - Handayani, Yulmi; Akib, Erwin; Quaraisy, Hidayah (Universitas Pakuan, 2024)
The purpose of this study was to determine the effect of applying the problem based learning model on students' critical thinking skills in social studies learning, this study used quantitative research with a pre-experimental type, the design used was the One group pretest posttest design. The population in this study were all Cluster I Kec. Mangala for the 2022/2023 school year. The selection of the sample in this study was carried out using a purposive sampling technique. The data that has been collected will be processed and analyzed using two types of analysis, namely descriptive statistical data analysis and inferential statistical data analysis. To assist in calculating the analysis of descriptive statistical data and inferential statistics, the SPSS application program version 25.0 is used. Based on the results of the study that in the learning process by applying the problem based learning model the teacher's ability to manage learning for 6 meetings was carried out very well, descriptively the application of the problem based learning model affected students' critical thinking skills in social studies subjects and in the learning process with applying the problem-based learning model, the teacher's ability to manage learning is carried out very well. with the results of the study using the one sample test obtained values with tcount = 18.159 ttable = 1.99 then H_0:μ_1≤60 is rejected and H_1:μ_1 60 is accepted in other words for a 95% confidence level average score of participants' critical thinking skills students after applying the problem-based learning model learning is more than 60 so it can be concluded that the application of problem-based learning model learning in meeting the criteria of completeness results in critical thinking skills that is more than 60.